2011
DOI: 10.1002/jcp.22509
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor-2 regulation of sprouty and NR4A genes in bovine ovarian granulosa cells

Abstract: Fibroblast growth factors (FGFs) alter ovarian function, at least in part by inhibiting steroid hormone secretion and affecting survival of granulosa cells. The mechanism of action of FGFs in ovarian follicle cells is largely unknown; in the present study we identified the major pathways used by FGF2 in non-luteinizing granulosa cells cultured under serum-free conditions. FGF2 increased abundance of mRNA encoding SPRY1, 2, and 4, but not SPRY3. Common pathways employed by FGF2 in the regulation of SPRY1, 2, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
27
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 55 publications
10
27
2
Order By: Relevance
“…In fact, recent data from our laboratory suggest the involvement of FGF2 in the regulation of meiosis progression, cumulus expansion and apoptosis (Buratini J.; 2017; Institute of Biosciences, São Paulo State University, Botucatu, SP, Brazil; unpublished data). Moreover, the involvement of FGF2 in the control of COC maturation is also consistent with our previous finding that FGF2 increases phosphorylation of extracellular signal-regulated kinase 1/2 (ERK1/2) and phosphoinositide-3-kinase/v-akt murine thymoma viral oncogene homolog (PI3K/AKT) in granulosa cells, two pathways known to regulate meiotic resumption and cumulus expansion (Jiang et al, 2011;Prochazka et al, 2012).…”
Section: Introductionsupporting
confidence: 91%
“…In fact, recent data from our laboratory suggest the involvement of FGF2 in the regulation of meiosis progression, cumulus expansion and apoptosis (Buratini J.; 2017; Institute of Biosciences, São Paulo State University, Botucatu, SP, Brazil; unpublished data). Moreover, the involvement of FGF2 in the control of COC maturation is also consistent with our previous finding that FGF2 increases phosphorylation of extracellular signal-regulated kinase 1/2 (ERK1/2) and phosphoinositide-3-kinase/v-akt murine thymoma viral oncogene homolog (PI3K/AKT) in granulosa cells, two pathways known to regulate meiotic resumption and cumulus expansion (Jiang et al, 2011;Prochazka et al, 2012).…”
Section: Introductionsupporting
confidence: 91%
“…In rat granulosa cells, FGF2 stimulated calcium signaling through a PKC dependent pathway (Peluso et al 2001), and in bovine granulosa cells FGF2 stimulated MAPK3/1 and Akt phosphorylation (Jiang et al 2011). In human granulosa lutein cells, FGF2 but not FGF4 or FGF10 increased SPRY2 mRNA levels (Haimov-Kochman et al 2005), whereas in bovine granulosa cells FGF2 and FGF4 stimulated SPRY2 mRNA abundance (Jiang et al 2011, Jiang & Price 2012. Several studies have demonstrated that FGF8 stimulates MAPK3/1 phosphorylation and SPRY2 mRNA levels in rat, human and mouse granulosa/ cumulus cells (Sugiura et al 2009, Miyoshi et al 2010, Jiang et al 2013.…”
Section: Intracellular Fgf Signaling In Granulosa Cellsmentioning
confidence: 99%
“…Horizontal lines indicate no effect; NA, data not available. Data from Miyoshi et al (2010), Jiang et al (2011Jiang et al ( , 2013 and Portela et al (2015). intracellular signaling and/or ii) interactions between FGFs, FGFRs, and HSPGs.…”
Section: The Basis For Divergent Signaling Of Related Fgfsmentioning
confidence: 99%
“…ERK-dependent SPRY2 expression has been reported in many studies [10,117,128,134,190,191]. However, it is not known whether this expression pattern depends on cell density.…”
Section: Spry2 Expression Controls Monolayer Integrity and Quiescencementioning
confidence: 99%